The consequences of early institutionalization: can institutions be improved? – should they? - McCall, Robert B. (2013)
BACKGROUND AND SCOPE: The focus of this review is on institutionalized children, one of the most inequitably and severely treated groups of children. Although institutions vary, many share some common characteristics, including large groups, high children: caregiver ratios, many and changing caregivers, and caregiver-child interactions that lack warm, sensitive, contingently-responsive, and child-directed behaviors. Resident children develop poorly physically, mentally, and social-emotionally, but those adopted from institutions display substantial catch-up growth in many domains of development. If they are adopted at an early age, there have been no long-term consequences of institutionalization yet measured; but if institutionalization is prolonged, they display higher rates of long-term deficiencies and problems in many domains. METHODS: This review is based on a database search of the literature, focusing on the development of children while residents, and the development of post-institutionalized children who have been transitioned from institutions to family care. It also draws on the reports and findings of the St. Petersburg–USA Orphanage Intervention. FINDINGS: A combination of theories pertaining to attachment (especially caregiver attachment to the infant/toddler), chronic stress, and genetics may explain these outcomes. It appears that caregiver-child interactions are a major contributor to children’s outcomes, and interventions in institutions that improve such interactions produce substantial increases in children’s physical, mental, and social-emotional development, including for children with disabilities. CONCLUSIONS: Deinstitutionalization and the creation of comprehensive professional child welfare systems emphasizing family care alternatives is a preferred goal, but this is likely to take many low-resource countries decades to develop. If substantial numbers of children remain in institutions despite best efforts to find families for them, improving the institutions might help to provide all the children with the best care possible under the circumstances.